2019
DOI: 10.1186/s13613-019-0616-6
|View full text |Cite
|
Sign up to set email alerts
|

Herpes simplex virus and Cytomegalovirus reactivation among severe ARDS patients under veno-venous ECMO

Abstract: Background: Herpesviridae reactivation among non-immunocompromised critically ill patients is associated with impaired prognosis, especially during acute respiratory distress syndrome (ARDS). However, little is known about herpes simplex virus (HSV) and Cytomegalovirus (CMV) reactivation occurring in patients with severe ARDS under veno-venous extracorporeal membrane oxygenation (ECMO). We tried to determine the frequency of Herpesviridae reactivation and its impact on patients' prognosis during ECMO for sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 27 publications
(60 reference statements)
2
33
0
Order By: Relevance
“…We read with interest of the report by Hraiech and colleagues [1] about the Herpesviridae reactivation among non-immunocompromised critically ill patients with acute respiratory distress syndrome (ARDS) supported with extracorporeal membrane oxygenation (ECMO). They found that Herpesviridae reactivation is frequent among patients with severe ARDS under ECMO and is associated with a longer duration of mechanical ventilation.…”
Section: Dear Editormentioning
confidence: 99%
See 4 more Smart Citations
“…We read with interest of the report by Hraiech and colleagues [1] about the Herpesviridae reactivation among non-immunocompromised critically ill patients with acute respiratory distress syndrome (ARDS) supported with extracorporeal membrane oxygenation (ECMO). They found that Herpesviridae reactivation is frequent among patients with severe ARDS under ECMO and is associated with a longer duration of mechanical ventilation.…”
Section: Dear Editormentioning
confidence: 99%
“…On the one hand, Herpesviridae reactivation may indicate an active infection and related damage to the organ function, which lead to a poor prognosis. However, in Hraiech's study [1], the definition of reactivation by a positive airway sample could not interpreted as true infection. And they reported that alveolar procollagen III level, an indicator of pulmonary fibrosis, was not different between both groups.…”
mentioning
confidence: 94%
See 3 more Smart Citations